Chemical Analysis of Fruit Juice of European Cranberrybush (Viburnum opulus) from Kayseri-Turkey - Soylak, M.; Elci, L.; Saracoglu, S.; Divrikli, U. (Asian Journal of Chemistry, 2010)
The fruit juice of the European cranberrybush (Viburnum opulus) is a traditional drink in middle Anatolia region of Turkey, especially in Kayseri city. Chemical analyses of fruit juice of Viburnum opulus (local name is Gilaboru) collected from the various sites in Kayseri-Turkey were performed. The major ions in the fruit juice were determined by the classical analytical methods. Trace metal contents of the fruit juice samples were determined by atomic absorption spectrometry. While major components of the samples were at mg/L level, the levels of the trace metal ion were found at μg/L.